2018
DOI: 10.3390/en11113145
|View full text |Cite
|
Sign up to set email alerts
|

A University Building Test Case for Occupancy-Based Building Automation

Abstract: Heating, ventilation and air-conditioning (HVAC) units in buildings form a system-of-subsystems entity that must be accurately integrated and controlled by the building automation system to ensure the occupants’ comfort with reduced energy consumption. As control of HVACs involves a standardized hierarchy of high-level set-point control and low-level Proportional-Integral-Derivative (PID) controls, there is a need for overcoming current control fragmentation without disrupting the standard hierarchy. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…With predictive HVAC control adapted to occupancy patterns, healthcare facilities can significantly improve energy efficiency and ensure patient comfort. These enhancements not only contribute to energy savings but also bolster the resilience of healthcare operations, crucial for emergency scenarios 5,6 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…With predictive HVAC control adapted to occupancy patterns, healthcare facilities can significantly improve energy efficiency and ensure patient comfort. These enhancements not only contribute to energy savings but also bolster the resilience of healthcare operations, crucial for emergency scenarios 5,6 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The grey-box models are combinations of white-box and black-box models. They rely on a simplified relationship of a physical process, and the parameters are regressed based on measured data and have been applied to model single energy technology, such as condensing boilers [191], thermal zone and HVAC systems [192] and building physics [193]. A high order grey-box implementation can be found in [169]: a 7R-4C model was implemented for an office building with years of measurement data, and is able to be solved by the built-in solver in MATLAB.…”
Section: Mpc Formulationmentioning
confidence: 99%
“…The study found that measured EUIs for 50% of the buildings deviated by about 25% from the projected performance, with 30% significantly better and 25% significantly worse [21]. Since most of the recent buildings HVAC systems controlled with a BAS system not only to collect data but to ensure occupant comfort [22]. Therefore, there has been an increase in the number of actual building performance data.…”
Section: Research Backgroundmentioning
confidence: 99%